The mediating effect of health literacy on COVID-19 vaccine confidence among a diverse sample of urban adults in Boston and Chicago. Issue 15 (6th April 2023) - Hurstak, Emily E.; Paasche-Orlow, Michael K; Hahn, Elizabeth A; Henault, Lori E.; Taddeo, Michelle A.; Moreno, Patricia I.; Weaver, Claire; Marquez, Melissa; Serrano, Eloisa; Thomas, Jessica; Griffith, James W.
Highlights: The relationship between race and ethnicity and vaccine confidence is mediated by health literacy. The relationship between education and vaccine confidence is mediated by health literacy. Increasing health literacy may improve vaccine confidence, which in turn may improve vaccination rates. Abstract: Background: A high rate of COVID-19 vaccination is critical to reduce morbidity and mortality related to infection and to control the COVID-19 pandemic. Understanding the factors that influence vaccine confidence can inform policies and programs aimed at vaccine promotion. We examined the impact of health literacy on COVID-19 vaccine confidence among a diverse sample of adults living in two major metropolitan areas. Methods: Questionnaire data from adults participating in an observational study conducted in Boston and Chicago from September 2018 through March 2021 were examined using path analyses to determine whether health literacy mediates the relationship between demographic variables and vaccine confidence, as measured by an adapted Vaccine Confidence Index (aVCI). Results: Participants ( N  = 273) were on average 49 years old, 63 % female, 4 % non-Hispanic Asian, 25 % Hispanic, 30 % non-Hispanic white, and 40 % non-Hispanic Black. Using non-Hispanic white and other race as the reference category, Black race and Hispanic ethnicity were associated with lower aVCI (−0.76, 95 % CI −1.00 to −0.50; −0.52, 95 % CI −0.80 to −0.27, total effects from a model excluding other covariates). Lower education was also associated with lower aVCI (using college or more as the reference, −0.73 for 12th grade or less, 95 % CI −0.93 to −0.47; −0.73 for some college/associate's/technical degree, 95 % CI −1.05 to −0.39). Health literacy partially mediated these effects for Black and Hispanic participants and those with lower education (indirect effects −0.19 and −0.19 for Black race and Hispanic ethnicity; 0.27 for 12th grade or less; −0.15 for some college/associate's/technical degree). Conclusions: Lower levels of education, Black race, and Hispanic ethnicity were associated with lower scores on health literacy, which in turn were associated with lower vaccine confidence. Our findings suggest that efforts to improve health literacy may improve vaccine confidence, which in turn may improve vaccination rates and vaccine equity. Clinical Trials Number: NCT03584490.